Death Drive and Critical Theory - Inara Luisa Marin (Critical Hermeneutics)
Much has been said about death drive in Critical Theory. This concept was mainly read as an aggressive and/or destructive drive. As a consequence, there are two ways of finding death drive in critical theories: the classic mode represented by Adorno, Horkheimer, Marcuse, and, more recently, Whitebook, in which death drive is seen as a factor that gives psychoanalysis its negativity face; or a way that leads to the despise of the nuclear function of death drive in psychoanalytic theory in name of normativity, as it happens in Fromm and Honneth. What I propose here is, from a comparison of both Freud’s texts, “Remembering, Repeating, and Working Through” (1914) and “Beyond the Pleasure Principle” (1920), to present a new way of appropriating the concept of death drive to produce a current critical theory. This means not considering the Wiederholungszwang as simply an imperative for coercion, but also a repetition compulsion. By proposing this reading of death drive (as suggested by Freud in 1920), I believe it is possible to amplify the range of possible connections between psychoanalysis and Critical Theory, keeping the negativity side, but without losing its normativity.